Crime, Punishment, and Schooling Decisions: Evidence from Colombian Adolescents - Ana Maria Ibanez; Catherine Rodriguez; David Zarruk (Inter-American Development Bank (IDB), 2013)
This paper uses a natural policy experiment to estimate how changes in the costs of engaging in criminal activity may influence adolescents' decisions in crime participation and school attendance. The study finds that, after an exogenous decrease in the severity of judicial punishment imposed on Colombian adolescents, crime rates in Colombian municipalities increased. This effect appears to be larger in municipalities with a higher proportion of adolescents between 14 and 15 years of age. The study provides suggestive evidence that one possible transmission channel for this effect is a decrease in the effort of the police force to capture teenage suspects. The study also finds that the probability that boys of this same age group attend school decreased following the change in the juvenile justice system. This effect is stronger for boys from homes where the heads of household are less educated.
Keywords: D19; I25; K14; 330